Early orthodontic and prosthetic treatment of a female patient with Velo-Cardio-Facial Syndrome – case report - Mąkal, Natalia; Majewska-Beśka, Sylwia; Bartczak, Jakub; Małkiewicz, Konrad (Forum Ortodontyczne / Orthodontic Forum, 2020)
Velo-Cardio-Facial Syndrome/DiGeorge syndrome is a medical condition requiring interdisciplinary treatment. It develops as early as in the foetal life, and is caused by deletion of a fragment of the long arm of chromosome 22. The most characteristic features of this syndrome include cardiac and/ or large vessel defects, lack of or hypoplasia of parathyroid glands, congenital immunodeficiencies caused by aplasia or lack of development of the thymus and intellectual disability of various degree. The developmental abnormalities of the facial skeleton include, among others, widely spaced palpebral fissures (hypertelorism), wide nasal bridge, small and narrow mouth with falling corners. The course of multispecialist treatment depends on the intensity of disorders in individual systems, including the stomatognathic system. Aim. The aim of the work is to present a case of a 7-yearold female patient diagnosed with DiGeorge syndrome, receiving interdisciplinary treatment. Material and methods. Patient’s medical records, including dental treatment records above all, were analysed. The literature search was mainly based on the PubMed database. Case report. A 7-yearold female patient diagnosed with DiGeorge syndrome presented at outpatient clinics of the Central Teaching Hospital, the Medical University of Łódź. A dental examination, including an orthodontic examination, showed dysmorphic facial features typical of 22q.11.2 microdeletion syndrome in an extraoral examination, and a malocclusion consisting in dental abnormalities complicated by extensive missing teeth in an intraoral examination. The patient was offered orthodontic, conservative treatment and prosthetic rehabilitation. Summary. Patients in the developmental age with DiGeorge syndrome require interdisciplinary treatment related to dental treatment. The treatment should include not only monitoring for caries and periodontitis, but also, if indicated, orthodontic and prosthetic rehabilitation aimed to restore functions and normal conditions of the development of the masticatory organ. (Mąkal N, Majewska-Beśka S, Bartczak J, Małkiewicz K. Early orthodontic and prosthetic treatment of a female patient with Velo-Cardio- Facial Syndrome – case report. Orthod Forum 2020; 16 (1): 45-55).